2016
DOI: 10.3390/atmos7050073
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Sources of Particulate Matter Measured near Houston, TX: Anthropogenic-Biogenic Interactions

Abstract: Particulate matter was measured in Conroe, Texas (~60 km north of downtown Houston, Texas) during the September 2013 DISCOVER-AQ campaign to determine the sources of particulate matter in the region. The measurement site is influenced by high biogenic emission rates as well as transport of anthropogenic pollutants from the Houston metropolitan area and is therefore an ideal location to study anthropogenic-biogenic interactions. Data from an Aerosol Chemical Speciation Monitor (ACSM) suggest that on average 64 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 61 publications
4
14
0
Order By: Relevance
“…The estimated ON accounted for 4 %-8 % of the total NR-PM 1 and 9 %-17 % of the OA in summer and 12 %-27 % of the total NR-PM 1 and 31 %-66 % percent of the OA in winter, comparable to other studies (Fry et al, 2009;Rollins et al, 2010;Xu et al, 2015;Berkemeier et al, 2016). A proxy for the NO q 3 production rate is based on the product of the observations of [NO 2 ] and [O 3 ] (Rollins et al, 2012), where brackets represent mixing ratios in parts per billion (ppb).…”
Section: Seasonal Variation Of the Formation Of Sulfate And Nitratesupporting
confidence: 87%
“…The estimated ON accounted for 4 %-8 % of the total NR-PM 1 and 9 %-17 % of the OA in summer and 12 %-27 % of the total NR-PM 1 and 31 %-66 % percent of the OA in winter, comparable to other studies (Fry et al, 2009;Rollins et al, 2010;Xu et al, 2015;Berkemeier et al, 2016). A proxy for the NO q 3 production rate is based on the product of the observations of [NO 2 ] and [O 3 ] (Rollins et al, 2012), where brackets represent mixing ratios in parts per billion (ppb).…”
Section: Seasonal Variation Of the Formation Of Sulfate And Nitratesupporting
confidence: 87%
“…If the aerosol particles were internally mixed, it would be reasonable to assume that rainfall would remove aerosol in approximately equal proportions. However, as discussed previously, aerosol sources are different between seasons, and there was a much larger biomass burning influence in the dry season (Martin et al, 2016), which is a known and significant source of OA (e.g., Jolleys et al, 2012;Bond et al, 2004;Yokelson et al, 2009;Ferek et al, 1998). Biomass burning was previously shown to emit particulate sulfate and nitrate directly, as well as NO x , sulfuric acid, and methane sulfonic acid (MSA), precursors of particulate nitrate and sulfate, but not in the same ratio as OA and its precursors (Yokelson et al, 2009).…”
Section: Wetmentioning
confidence: 89%
“…Measurements of acetonitrile (m/z 42), whose major source is biomass burning (Yokelson et al, 2009(Yokelson et al, , 2007, are 2-3 times higher in the dry season than the wet season, indicating a significant biomass burning impact in the region. Biomass burning is a known source of OA (Jolleys et al, 2012;Bond et al, 2004;Yokelson et al, 2009;Ferek et al, 1998) and would also contribute to the higher aerosol concentrations observed in the dry season. The aerosol mass loadings we measure in the dry season are consistent with aircraft-based AMS measurements made during the SAMBBA campaign at the same time of year, though several hundred kilometers to the SW in the state of Rondônia (Allan et al, 2014).…”
Section: Overview Of G-1 Aerosol Data and Comparison Of Wet And Dry Smentioning
confidence: 99%
“…k H is the second-order rate constant of the reaction scaled by the number of weakest C-H bonds. The method relies on BDEs as input for the correlation, which can be estimated reliably with a precision of ±8 kJ mol −1 (Benson, 1976). The method by Benson (1976) estimates the strength of a bond as a function of the adjacent atoms/molecular groups.…”
Section: Evans-polanyi-type Correlationsmentioning
confidence: 99%